PERCEIVED NEIGHBORHOOD ENVIRONMENT AND LEFT ATRIAL MEASURES IN THE JACKSON HEART STUDY. (11th November 2018) - Rooks, R; Havranek, E; Hill, A; Ford, C; Clark, C; Robinson, J; Fox, E; Sims, M
Abstract: Research on neighborhood environments and cardiovascular diseases (CVDs) suggest living in disadvantaged neighborhoods increases CVD risk, independent of individual risk. As long-term neighborhood residents, middle-older aged African-Americans often have greater cumulative environmental exposures than younger African-Americans. Atrial size is a predictor of multiple CVDs, including atrial fibrillation and stroke. We hypothesized: 1) disadvantaged neighborhood environments are related to greater left atrial (LA) size and volume and 2) these relationships vary by age. We used multivariable linear regression to examine relationships between perceived neighborhood social environments (e.g., neighborhood social cohesion, neighborhood violence, and neighborhood problems) and LA measures [e.g., LA size using M-mode echo diameter/height (n=3, 048) and 2D echo LA area/height (n=5, 018), and LA volume using M-mode echo LA diameter/body surface area (n=3, 047)] among African-Americans in exam 1 (2000–2004) of the Jackson Heart Study. We adjusted models for demographics, behaviors, systolic and diastolic blood pressure, blood pressure medications, left ventricular mass, body mass index, and diabetes. In unadjusted analyses, all relationships were significant except between neighborhood social cohesion and LA size or volume. However, after adjustments (full model), no significant relationships were evident between neighborhood environments and LA measures or in the age-stratified models. Since we found no evidence for age variation in the relationships examined, our results do not support a cumulative neighborhood stress effect on LA size and volume for middle-older aged African-Americans. Beyond perceptions, understanding the objective environmental context, length of environmental exposures, and longitudinal pathways involved in developing CVD risk may be important next steps.